Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja karyawan Bagian Produksi Pengolahan PTPN III Rantauprapat - Servina Siregar; Sjahril Effendy; Syafruddin Ritonga (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the effect of work motivation and work discipline on the performance of employees of the Processing Production Division of PTPN III Rantauprapat. The hypothesis proposed is the influence of work motivation and work discipline on the performance of the employees of the Processing Production Division of PTPN III Rantauprapat. The number of samples in this study was 119 people. Sampling technique using Total Sampling. The data collection method is a Likert scale of work motivation, work discipline, and employee performance. Data analysis used multiple regression linear analysis model. The results of this study are: There is a significant influence between work motivation on employee performance. This is indicated by the t-count value of Work Motivation of 7.832 > ttable 1.980 and the Sig value of 0.000 <0.025. There is a significant influence between Work Discipline on Employee Performance. This is indicated by the coefficient of the t value of Work Discipline which is 3,410 > ttable 1,980 and the Sig value of 0.001 < 0.025. There is a significant influence between Work Motivation and Work Discipline Employee Performance. This is indicated by the calculated F value of 66,112 > F table 19,487 and the significance value of 0.000 with p value <0.05